Alpha2-Adrenoblockers Regulate Development of Oxidative Stress and Cognitive Behaviour of Rats under Chronic Acoustic Stress Conditions - Magdalina Melkonyan; Ashkhen Manukyan; Lilit Hunanyan; Artem Grigoryan; Hayk Harutyunyan; Lilit Sukiasyan; Lusine Danielyan; Konstantin Yenkoyan (MDPI AG, 2021)
Noise is a wide-spread stress factor in modern life produced by urbanization, traffic, and an industrialized environment. Noise stress causes dysfunction and neurotransmission impairment in the central nervous system, as well as changes in hormone levels. In this study, we have examined the level of α-Tocopherol (α-T) and malondialdehyde (MDA) in plasma and the erythrocytes' membrane (EM), as well as the behavioral characteristics of a noise-induced stress model in rats. In addition, the modulating effect of α2-adrenoblockers, beditin, and mesedin on the aforementioned parameters has been investigated. For these purposes, albino male rats were divided into four groups: (1) untreated; (2) noise-exposed, (3) noise-exposed and beditin-treated (2 mg/kg, i.p.), and (4) noise-exposed and mesedin-treated (10 mg/kg, i.p.) animals. Noise-exposed groups were treated with 91dBA noise on 60 days with a daily duration of 8 h. Increased MDA and decreased α-T levels in plasma and EM were observed upon chronic high-level noise exposure. Locomotor and behavioral activity assessed with a Y-maze revealed disorientation and increased anxiety under chronic noise exposure. Prominently, α2-adrenoblockers alleviated both behavioral deficits and oxidative stress, providing evidence for the involvement of α2-adrenoceptor in the pathophysiology of noise-induced stress.